Influence of strain induced by AlN nucleation layer on the electrical properties of AlGaN/GaN heterostructures on Si(111) substrate - Dennis Christy; Arata Watanabe; Takashi Egawa (AIP Advances, 2014)
The crack-free metal-organic chemical vapor deposition (MOCVD) grown AlGaN/GaN heterostructures on Si substrate with modified growth conditions of AlN nucleation layer (NL) and its influence on the electrical and structural properties of conductive GaN layer are presented. From the Hall electrical measurements, a gradual decrease of two-dimensional electron gas (2DEG) concentration near heterointerface as the function of NL thickness is observed possibly due to the reduction in difference of piezoelectric polarization charge densities between AlGaN and GaN layers. It also indicates that the minimum tensile stress and a relatively less total dislocation density for high pressure grown NL can ensure a 20 % increment in mobility at room temperature irrespective of the interface roughness. The thickness and pressure variations in NL and the subsequent changes in growth mode of AlN contributing to the post growth residual tensile stress are investigated using X-ray diffraction and Raman scattering experiments, respectively. The post growth intrinsic residual stress in top layers of heterostructures arises from lattice mismatches, NL parameters and defect densities in GaN. Hence, efforts to reduce the intrinsic residual stress in current conducting GaN layer give an opportunity to further improve the electrical characteristics of AlGaN/GaN device structures on Si.